Shortcuts in Word 2000 - Etherington, Sue (Dorling Kindersley, 2000)
This user-friendly visual guide contains over 100 time-saving shortcuts for Microsoft Word. Master the basics of using Word more quickly and effectively, and learn how to customise tool bars and Word features